Postfire recovery of forest litter in Scots pine forests in two different regions of boreal zone. - Gorshkov, Vadim V.; Bakkal, Irene J.; Stavrova, Natalie I. (The Finnish Society of Forest Science and The Finnish Forest Research Institute, 2009)
Part I Climate Change Investigations carried out in the Kola peninsula (northern taiga) and in the South-western part of Western Siberia (southern taiga and forest-steppe) revealed identical course of the postfire restoration process of forest litter thickness in Scots pine forests. Despite the differences in mean annual temperature (2 °C) and other climatic characteristics the recovery time for thickness of forest litter in both regions amounts to 90–100 years after fire in pine forests of lichen site type and 120–140 years – in green moss type; the thickness of forest litter therewith corresponds 3–4 cm and 7–8 cm respectively. That means that within the natural borders of pine forests, communities of a specific type possess uniform characteristics of restoration. On the basis of empirical data it appears that the predicted increase of mean annual temperature of earth surface by (2 °C) will not bring changes into the character of postfire recovery of forest litter thickness. It was shown that during the period of the recovery, which spans about 90 years after fire in pine forests of lichen and green moss–lichen site types and 140 years in ones of green moss site types, the rate of increasing of carbon store in the forest litter averaged 0.6 t ha–1 year–1, 0.1 t ha–1 year–1 and 0.2 t ha–1 year–1, respectively.